Impact Analysis of Information and Communication Technology (ICT) on Diplomacy - Aadil Ahmad Shairgojri (Journal of Learning and Educational Policy, 2022)
Science and Technology (S&T) were aggressively used for more than two decades during the Cold Conflict between the United States and the former Soviet Union to avert war and maintain diplomatic equilibrium in the conduct of 'International Relations' (I.R.). The prevalence of soft power in digital age politics and the empowerment of non-state actors in international relations are both aided by access to information and control over it. Aside from increased roles, requests for expanded outreach and accountability, and dwindling resources, the modern diplomatic service is particularly challenged by the multistakeholder and interdisciplinary international arena. The well-planned and well-organized use of ICT may empower diplomatic services, particularly in small and developing nations, and assist them in dealing with rising difficulties and delivering their full potential. The study goes into great detail regarding how science and technology affect diplomacy.